2020
DOI: 10.1002/er.5266
|View full text |Cite
|
Sign up to set email alerts
|

Rapid degradation characteristics of an air‐cooled PEMFC stack

Abstract: Summary Durability is one of the obstacles to the large‐scale commercialization of proton exchange membrane fuel cell (PEMFC) stacks. Understanding its decay behavior is a prerequisite for improving durability. In this study, rapid degradation characteristics of an air‐cooled PEMFC stack are investigated. Due to the simultaneous presence of various degradation sources, the maximum power of the PEMFC stack has been reduced by 39.6% after just 74.6 h of operations. Performance degradation characteristics are sou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…DOE‐suggested degradation targets usually require less than 10% loss in the efficiency of an FC system at the end of its lifetime. The degradation mechanisms can basically be subdivided into two families: FC component degradation (membrane, electrocatalysts and catalyst loading or CL, GDL, gaskets, bipolar plates or BPs, sealing) and degradation effects due to operative conditions (air/fuel impurities, load cycle, startup/shutdown, environmental subfreezing conditions) 177‐179 . Membranes can degrade mechanically, thermally, or chemically electrochemically 143 .…”
Section: Degradation Of Fcsmentioning
confidence: 99%
“…DOE‐suggested degradation targets usually require less than 10% loss in the efficiency of an FC system at the end of its lifetime. The degradation mechanisms can basically be subdivided into two families: FC component degradation (membrane, electrocatalysts and catalyst loading or CL, GDL, gaskets, bipolar plates or BPs, sealing) and degradation effects due to operative conditions (air/fuel impurities, load cycle, startup/shutdown, environmental subfreezing conditions) 177‐179 . Membranes can degrade mechanically, thermally, or chemically electrochemically 143 .…”
Section: Degradation Of Fcsmentioning
confidence: 99%
“…By reversing the polarity of the cell, a reverse current flow through the PEMFC generates heat. This may cause degradation within the cell after several uses [15,26,27]. Therefore, this solution is not ideal for the subfreezing start-up of a PEMFC despite its simplicity as well as its low weight and volume.…”
Section: Introductionmentioning
confidence: 99%
“…Their study indicates that different GDL design approaches would significantly affect the flow pattern of water, which in turn influences the performance of fuel cells. Luo et al 24 found that the performance of PEMFC was degraded with the reduced contact angle of the GDL, and the adhesion of impurities caused water management problems.…”
Section: Introductionmentioning
confidence: 99%